Effect of employees’ competency, risk culture and organisational innovativeness on enterprise risk management implementation / Erlane K Ghani, Syazween Farisya Harun and Kamaruzzaman Muhammad - Ghani, Erlane K; Harun, Syazween Farisya; Muhammad, Kamaruzzaman (Faculty of Accountancy, 2019)
Enterprise Risk Management (ERM) is an important tool in assessing risks within the organization. As such, most organizations would like to have a proper risk management policy, but often do not have one. Competency, risk culture and organizational innovativeness are highly broad areas that are related to the implementation of enterprise risk management in an organization. The level of successful implementation of ERM can give a high impact on the profitability of the organization. Therefore, in order to achieve a successful implementation of ERM, it is important to know the core factors that affect the implementation of the ERM in an organization. This study aims to assess the factors that influence ERM implementation among public listed companies in Malaysia. Specifically, this study examines the influence of employees’ competency, risk culture and organizational innovativeness on ERM implementation in public listed companies. Based on the 640 responses received from various public listed companies under the manufacturing companies in Malaysia, this study shows that employees’ competency and organizational innovativeness have a positive relationship with the successful implementation of ERM. On the other hand, risk culture was shown to have an insignificant relationship with the implementation of ERM. In this regard, the management of the public listed companies should focus more on organizational innovativeness for successful ERM implementation and provide more training for their employees in order to develop the potential in each of their employees.